Aplikasi Inventory Obat-Obatan Berbasis Web di Pusat Kesehatan Masyarakat - Lontoh, Patrick Rodney; Sambul, Alwin M.; Wowor, Hans (Jurnal Teknik Informatika, 2021)
Abstract — Public Health Center certainly have various kinds of drugs that will be given to patients seeking treatment at the Public Health Center. Given the drugs contained in the Public Health Center is one of the important factors in the Public Health Center. Therefore, it is necessary to have effective and efficient drug data management so as to improve the performance of the agency. To facilitate the management of drug data, the authors designed a web-based drugs inventory application at the Public Health Center to manage drug data in the Public Health Center along with their income and expenditure. In this application there is only one user who is the administrator himself, but the author provides a feature if there are other officers on duty. The facilities they have are entering data in and out of drugs, entering new drug data, and viewing information on existing drugs as a whole for both incoming, supply and even existing demand. Based on the application design, in this thesis the author uses web programming languages, namely HTML, CSS, PHP, BOOTSTRAP as a template and MySQL as a database storage. The test results use the black box and beta testing methods to assess every feature provided by the author in making the application. Making this application is expected to be implemented in the work in order to facilitate the work so that the work is more efficient and effective. Keywords — Application, Inventory, Public Health Center Stock, Website.